RELATIONSHIP BETWEEN SAFE DISCHARGE AND GROUNDWATER ZONING IN PRODUCTION WELLS AT PT MONOKEM SURYA RENGASDENGKLOK DISTRICT, KARAWANG REGENCY, WEST JAVA PROVINCE - Inayat Puspawardhana, Danang
PT Monokem Surya utilizes water to process zircon ore which is entirely sourced from groundwater with a minimum requirement of 550 m3/day. The source of groundwater comes from 7 drilled wells, all of which extracted a water from the confined aquifer layer. A study is needed to determine the potential of groundwater and aquifer parameters from wells with a pumping test. To determine the groundwater potential in the form of optimum discharge, a step drawdown test was carried out for all wells, and a 72-hour constant rate test was carried out to determine several aquifer parameters in 3 wells which were considered representative of other wells and also in field conditions it is possible to carry out the test. After discovering the aquifer parameters and optimum discharge, simultaneous pumping simulations were carried out for all wells and resulted in drawdowns that were generally not classified as safe criteria. Furthermore, a trial and error re-simulation is carried out to make drawdown that fall within the safe criteria with a well efficiency limit of not less than 70%, and several pumping schemes are made to produce various alternatives that can be applied at the research location, namely, pumping schemes simultaneously in 7 wells, pumping scheme is in rotation for 8 hours, and the pumping scheme is in rotation for 10 hours. These three simulations produced groundwater of 513.68 m3/day in the simultaneous simulation, 472.32 m3/day in the 8-hour rotation simulation, and 540.12 m3/day in the 10-hour rotation simulation. These results do not meet the minimum water needs, so other water sources are needed to cover these needs. Based on the values of several aquifer parameters, the groundwater potential at the research location can be classified into the moderate class. Keywords: confined aquifer, aquifer parameter, drawdown, groundwater potential, pumping test